Plasmodium DNA-mediated TLR9 activation of T-bet+ B cells contributes to autoimmune anaemia during malaria. Issue 1 (December 2017) - Rivera-Correa, J.; Guthmiller, J.; Vijay, R.; Fernandez-Arias, C.; Pardo-Ruge, M.; Gonzalez, S.; Butler, N.; Rodriguez, A.
Abstract Infectious pathogens contribute to the development of autoimmune disorders, but the mechanisms connecting these processes are incompletely understood. Here we show thatPlasmodium DNA induces autoreactive responses against erythrocytes by activating a population of B cells expressing CD11c and the transcription factor T-bet, which become major producers of autoantibodies that promote malarial anaemia. Additionally, we identify parasite DNA-sensing through Toll-like receptor 9 (TLR9) along with inflammatory cytokine receptor IFN-γ receptor (IFN-γR) as essential signals that synergize to promote the development and appearance of these autoreactive T-bet+ B cells. The lack of any of these signals ameliorates malarial anaemia during infection in a mouse model. We also identify both expansion of T-bet+ B cells and production of anti-erythrocyte antibodies in ex vivo cultures of naive human peripheral blood mononuclear cells (PBMC) exposed toP. falciprum infected erythrocyte lysates. We propose that synergistic TLR9/IFN-γR activation of T-bet+ B cells is a mechanism underlying infection-induced autoimmune-like responses. Autoimmune anaemia often accompaniesPlasmodium infection and malaria, but how anaemia is induced is still unclear. Here the authors show that Plasmodium DNA, together with interferon-γ, can activate B cells to induce auto-antibodies that recognize red blood cells and promote their removal to contribute to anaemia onset.